Optical Coherence Tomography Angiography Findings After Intravitreal Ranibizumab in Patients With Coats Disease - Cennamo, Gilda; Montorio, Daniela; Comune, Chiara; Laezza, Maria Paola; Fallico, Matteo; Lionetti, Maria Elena; Reibaldi, Michele (Frontiers in Medicine, 2021)
The aim of this retrospective study was to describe the vascular features in eyes with Coats disease, using optical coherence tomography angiography (OCTA), at baseline and after three monthly intravitreal injections of ranibizumab. Fifteen eyes of 15 consecutive patients affected by Coats’ disease were recruited in this study. All patients underwent the best-corrected visual acuity (BCVA) evaluation, fundus examination, fluorescein angiography (FA), indocyanine green angiography (ICGA), multicolor imaging, structural Spectral Domain (SD)-OCT and OCTA at baseline and 1 month after the third monthly ranibizumab injection (loading phase). Fifteen patients completed the study, of whom 9 were males and 6 females. Mean age was 20.4 ± 2 years. BCVA was 0.46 ± 0.11 logMar and 0.47 ± 0.12 logMar at baseline and after treatment, respectively (p=0.164). SD-OCT revealed no significant decrease in central macular thickness (486.33 µm ± 93.37 at baseline vs 483.4 µm ± 80.97 after treatment; p=0.915). The subretinal exudates persisted in macular region after intravitreal injections. OCTA showed a general vascular rarefaction in superficial capillary plexus (SCP), deep capillary plexus (DCP) and choriocapillary (CC) that did not change after loading phase. This study showed no functional and vascular improvement following 3 monthly ranibizumab injections. OCTA, non-invasive technique, could be useful during follow up of these patients and provide a better understand of pathogenesis of this disorder.